Met signaling in cardiomyocytes is required for normal cardiac function in adult mice - Arechedera, María; Carmona-Mejías, Rita María; González-Núñez, María; Gutiérrez-Urquiza, Álvaro; Bragado, Paloma; Cruz-González, Ignacio; Cano, Elena; Guerrero, Carmen; Sánchez, Aránzazu; López-Novao, José Miguel; Schneider, Michael D.; Maina, Flavio; et al. (Elsevier, 2013)
Hepatocyte growth factor (HGF) and its receptor, Met, are key determinants of distinct developmental processes. Although HGF exerts cardio-protective effects in a number of cardiac pathologies, it remains unknown whether HGF/Met signaling is essential for myocardial development and/or physiological function in adulthood. We therefore investigated the requirement of HGF/Met signaling in cardiomyocyte for embryonic and postnatal heart development and function by conditional inactivation of the Met receptor in cardiomyocytes using the Cre-α-MHC mouse line (referred to as α-MHCMet-KO). Although α-MHCMet-KO mice showed normal heart development and were viable and fertile, by 6 months of age, males developed cardiomyocyte hypertrophy, associated with interstitial fibrosis. A significant upregulation in markers of myocardial damage, such as β-MHC and ANF, was also observed. By the age of 9 months, α-MHCMet-KO males displayed systolic cardiac dysfunction. Mechanistically, we provide evidence of a severe imbalance in the antioxidant defenses in α-MHCMet-KO hearts involving a reduced expression and activity of catalase and superoxide dismutase, with consequent reactive oxygen species accumulation. Similar anomalies were observed in females, although with a slower kinetics. We also found that Met signaling down-regulation leads to an increase in TGF-β production and a decrease in p38MAPK activation, which may contribute to phenotypic alterations displayed in α-MHCMet-KO mice. Consistently, we show that HGF acts through p38α to upregulate antioxidant enzymes in cardiomyocytes. Our results highlight that HGF/Met signaling in cardiomyocytes plays a physiological cardio-protective role in adult mice by acting as an endogenous regulator of heart function through oxidative stress control.
Keywords: Cardiología; Hepatocyte growth factor; Met; Cardiomyocytes; Oxidative stress; Heart; p38MAPK